Studi Performansi Alat Pemanas Air dengan Menggunakan Kolektor Surya Plat Datar - Darwin Darwin; Hendri Syah; Sujan Yadi (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
This study aims to analyze the performance of the water heater using solar collector flat plate type. Efficiency performance of solar collectors in the process of heating the water also becomes the main focus in this study. This study was conducted with two experiments consisting of a flat plate solar collector with horizontal and flat plate solar collector with tilt angle 22o. Experiments carried out with 8 hours of testing within 6 days. Water was circulated into the collector pipe using a pump capacity of 125 Watts. From the research it is known that the amount of electrical energy required by pump for 6 days with 8 -hour time trial experiment, was about 21.6 MJ. The rate of flow of the fluid in the collector pipe is 2x10 - 5 m3/s. The plate solar collector with a slope of 22o reached the highest average temperature in the third experiment, which was about 64.7 ° C; however, the lowest average temperature was found in the horizontal collector (0o) at the third experiment, which was about 47.5 ° C. It was found that the highest efficiency obtained at the collector plate with 22o tilt angle was equal to 76 % while the lowest efficiency was obtained at a horizontal collector with an efficiency of 53.6 %. Keywords: solar collectors, flat plate, water heater